Neuronal-glial populations form functional networks in a biocompatible 3D scaffold. (16th November 2015) - Smith, Imogen; Haag, Marcus; Ugbode, Christopher; Tams, Daniel; Rattray, Marcus; Przyborski, Stefan; Bithell, Angela; Whalley, Benjamin J.
Highlights: We examine mixed CNS cultures in a biocompatible 3D scaffold. We compare 3D cultures with conventional monolayer cultures. Glial morphology in 3D cultures is more consistent with that seen in vivo . 3D cultures form functional neuronal networks. 3D cultures exhibit spontaneous local field potentials. Abstract: Monolayers of neurons and glia have been employed for decades as tools for the study of cellular physiology and as the basis for a variety of standard toxicological assays. A variety of three dimensional (3D) culture techniques have been developed with the aim to produce cultures that recapitulate desirable features of intact. In this study, we investigated the effect of preparing primary mouse mixed neuron and glial cultures in the inert 3D scaffold, Alvetex. Using planar multielectrode arrays, we compared the spontaneous bioelectrical activity exhibited by neuroglial networks grown in the scaffold with that seen in the same cells prepared as conventional monolayer cultures. Two dimensional (monolayer; 2D) cultures exhibited a significantly higher spike firing rate than that seen in 3D cultures although no difference was seen in total signal power (<50 Hz) while pharmacological responsiveness of each culture type to antagonism of GABAA R, NMDAR and AMPAR was highly comparable. Interestingly, correlation of burst events, spike firing and total signal power (<50 Hz) revealed that local field potential events were associated with action potential driven bursts as was the case for 2D cultures. Moreover, glial morphology was more physiologically normal in 3D cultures. These results show that 3D culture in inert scaffolds represents a more physiologically normal preparation which has advantages for physiological, pharmacological, toxicological and drug development studies, particularly given the extensive use of such preparations in high throughput and high content systems.